Extraadrenal steroid 21-hydroxylation is not mediated by P450c21. - Mellon, S H (1989)
The 21-hydroxylation of progesterone to deoxycorticosterone (DOC) and of 17-hydroxyprogesterone to 11-deoxycortisol in the human adrenal cortex is mediated by a single enzyme termed P450c21. Extraadrenal tissues can clear circulating progesterone and progesterone sulfate by 21-hydroxylation to DOC and DOC-sulfate. It has previously been established that such extraadrenal 21-hydroxylase activity is widely distributed in adult and fetal tissues, but it has not been known if extra-adrenal 21-hydroxylation is mediated by the same P450c21 enzyme found in the adrenal. We examined human RNA from fetal adrenal, liver, kidney, lung, brain, heart, skin, spleen, testis, and placenta by solution hybridization to human P450c21 probes transcribed from cloned human P450c21 cDNA, followed by nuclease protection and acrylamide gel electrophoresis. No P450c21 mRNA was detectable in any extraadrenal tissue. The sensitivity of the assay would have detected P450c21 mRNA at 0.01% of its abundance in the human fetal adrenal. Similar experiments in rats showed no P450c21 mRNA in brain, heart, kidney, liver, lung, testis, ovary, or uterus. These results clearly demonstrate that one or more enzymes other than the classical adrenal 21-hydroxylase are responsible for human and rat extraadrenal 21-hydroxylation.